(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In graph theory coloring plays a major role. The vertex coloring is an assignment of colors to the vertices of a graph ‘G’ such that no two adjacent vertices have the same color. That is, no two vertices of an edge should be of the same color. In this study, strong coloring for various standard graphs are derived and further using suitable examples the results are examined.